1980
DOI: 10.1364/ol.5.000282
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-spectral-brightness tunable XUV radiation at 83 nm

Abstract: High-spectral-brightness coherent XUV radiation has been produced by third-harmonic generation of a transformlimited- bandwidth KrF* laser in gaseous xenon. The observed XUV output, which was continuously tunable from 82.8 to 83.3 nm, had a peak power of 40 mW, a bandwidth <0.01 cm(-1), and absolute frequency control to within 0.04 cm(-1). The utility of this XUV source for high-resolution spectroscopic applications is demonstrated by absorption studies in molecular hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The feasibility of such XUV sources for spectroscopic applications has been demonstrated very recently in accurate measurements of relative photoionization cross sections and autoionization profiles (Balcou et al 1995). The above-mentioned work includes a comparison to wave-mixing with tunable lasers of long pulse duration (Egger et al 1980, Hilbig et al 1982, Bokor et al 1983, Page et al 1987 and its applications to spectroscopy (Miyazaki et al 1989, Cromwell et al 1989, Marangos et al 1990, Eikema et al 1993.…”
mentioning
confidence: 99%
“…The feasibility of such XUV sources for spectroscopic applications has been demonstrated very recently in accurate measurements of relative photoionization cross sections and autoionization profiles (Balcou et al 1995). The above-mentioned work includes a comparison to wave-mixing with tunable lasers of long pulse duration (Egger et al 1980, Hilbig et al 1982, Bokor et al 1983, Page et al 1987 and its applications to spectroscopy (Miyazaki et al 1989, Cromwell et al 1989, Marangos et al 1990, Eikema et al 1993.…”
mentioning
confidence: 99%
“…Among them are: (1) ionic rare-gas alkali excimers which are isoelectronic to the rare-gas dimers, (2) and quartet levels of the alkali atoms or ions ,which retain metastability against autoionization and radiate quite strongly in the XUV.…”
Section: Future Vuv/xuv Laser Researchmentioning
confidence: 99%
“…85 Slabko et al 111 have used one that involves a two-photon resonance with the 6s8s 1 S 0 state for radiation from the fourth harmonic of an N d : glass laser to generate tunable radiation near 89.6 nm. 85 Slabko et al 111 have used one that involves a two-photon resonance with the 6s8s 1 S 0 state for radiation from the fourth harmonic of an N d : glass laser to generate tunable radiation near 89.6 nm.…”
Section: Generation Of Vuv Radiation By Anti-stokes-raman Scatteringmentioning
confidence: 99%
“…Egger et al 111 and Rothschild et al 112 have reported third-harmonic conversion of radiation from a K r F laser in Xe, producing radiation near 83 nm. R e i n t j e s 1 0 8 -1 1 0 has reported the generation of radiation near 102.6 nm by third-harmonic conversion of radiation from an XeCl laser in Ar and Kr.…”
Section: Extreme Ultraviolet Radiationmentioning
confidence: 99%